James D. Faubion, George E. Marcus (ed). Fieldwork Is Not What It Used to Be:Learning Anthropology's Method in a Time of Transition - Potkonjak, Sanja (Array, 2009)
Prikaz se osvrće na probleme konceptualiziranja antropološkog terena u suvremenosti.